2006
DOI: 10.1016/j.cmet.2006.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Non-DNA binding, dominant-negative, human PPARγ mutations cause lipodystrophic insulin resistance

Abstract: SummaryPPARγ is essential for adipogenesis and metabolic homeostasis. We describe mutations in the DNA and ligand binding domains of human PPARγ in lipodystrophic, severe insulin resistance. These receptor mutants lack DNA binding and transcriptional activity but can translocate to the nucleus, interact with PPARγ coactivators and inhibit coexpressed wild-type receptor. Expression of PPARγ target genes is markedly attenuated in mutation-containing versus receptor haploinsufficent primary cells, indicating that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
150
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(160 citation statements)
references
References 67 publications
4
150
1
3
Order By: Relevance
“…Finally, as mentioned above, point mutations in the ligand or DNA-binding domain of PPAR are associated with severe insulin resistance in human subjects [26,27]. The majority of data also supports the conclusion that WAT is the principal tissue responsible for the therapeutic effects of TZDs although extra-adipose actions also contribute to improved insulin sensitivity.…”
Section: Ppar and Insulin Resistancesupporting
confidence: 57%
See 1 more Smart Citation
“…Finally, as mentioned above, point mutations in the ligand or DNA-binding domain of PPAR are associated with severe insulin resistance in human subjects [26,27]. The majority of data also supports the conclusion that WAT is the principal tissue responsible for the therapeutic effects of TZDs although extra-adipose actions also contribute to improved insulin sensitivity.…”
Section: Ppar and Insulin Resistancesupporting
confidence: 57%
“…Naturally occurring PPAR mutations in human subjects also support an important role for this transcription factor in WAT development [26,27]. Specifically, individuals carrying dominant-negative mutations in PPAR display partial lipodystrophy concomitant with insulin resistance, dys-lipidaemia, and hypertension.…”
Section: Ppar and Adipocyte Biologymentioning
confidence: 96%
“…For P12A, the variant is very common, but the magnitude of effect on disease risk is modest (20% decreased risk of T2D) (3). In rare families with syndromic lipodystrophy, loss-of-function (LOF) mutations in PPARG that prohibit adipocyte differentiation in vitro, have been found that segregate with lipodystophy, insulin resistance, and T2D (4,5). The magnitude of effect on individual and cellular phenotypes is strong, but the mutations are extremely rare.…”
mentioning
confidence: 99%
“…1) (Chan et al, 2010;Zieleniak et al, 2008). Single amino acid mutations within these functional domains result in severe defects in PPAR function that affect lipid metabolism and insulin resistance (Agostini et al, 2006;Barroso et al, 1999;Hegele et al, 2002;Ristow et al, 1998). PPAR heterodimerization with RXRs leads to binding of the peroxisome proliferator response element independent of ligand.…”
Section: Introductionmentioning
confidence: 99%